Evaluación de cuatro tipos de sustratos y tres niveles de humus en la obtención de plántulas de nogal (juglans neotrópica) en la zona de Otavalo, Provincia de Imbabura. - Cabascango Cabascango, Marco Vinicio (2011)
he present investigation on “Evaluation of four types of bases and three levels of humus in the obtaining of walnut plántulas (Juglans neotrópica) in the area of Otavalo, county of Imbabura”, it was located in the canton Otavalo, County of Imbabura to 100 meters of the Pan-American north, Agricultural school “Carlos Ubidia Albuja.” As siembra material walnut seed was used (Juglans neotropica) fully adapted to the area. Bases like humus were studied, husk of rice; pomina; sand and black earth, in levels of 25, 50 and 75%. The design blocks was used totally at random (DBCA), with thirteen treatments and four repetitions. The comparison of the averages of the variables was obtained with the test from Tukey to 95% of probability.